Bhutan in pursuit of gross national happiness - Griffiths, Steven; Information Office Asian Development Bank. (Manila Asian Development Bank, 1996)
For centuries, Bhutan had been closed to the outside world. It was only about 30 years ago that the landlocked Himalayan kingdom emerged from a self-imposed isolation. Until then there were no schools, no electricity and no roads, only mountain trails linking Bhutan with neighboring India and China. Since development started in the early sixties, the country has achieved considerable economic growth. Yet, Bhutan has been deliberately pursuing a cautious path if development to preserve iys unique culture and traditional values and protect its fragile environment. Bhutan is endowed with vast mineral and forest resources, which, as a matter of policy remain largely unexploited. "In Pursuit of Gross National Happiness" explores how Bhutan which has been declared a role model in sustainable development. is balancing heritage and development.
With 1 converted disc.
Scriptwriter, Ian Gill ; Narrator, Robert Salamon ; Online editor, Roberto Regalado.
VHS.
In Dzongkha, with English subtitle.